Upaya Meningkatkan Hasil Belajar Matematika Materi Menghitung Luas Bangun Datar Melalui Model Pembelajaran Numbered Heads Together (NHT) pada Siswa Kelas VI Semester I SD Negeri Karanggedong Kecamatan Ngadirejo Kabupaten Temanggung Tahun Pelajaran 2015/2016 - Ida Widiyawati (Universitas PGRI Semarang, 2019)
The background of this study is the low student learning outcomes mathematics subject matter calculating the area of flat shapes, students do not have the motivation to learn, learning activities are not interactive and less interesting because the teacher in learning has not used an innovative learning model and has not used the cooperative type model Numbered Head Together (NHT). The purpose of this study was to improve mathematics learning outcomes in calculating flat area in grade VI students of semester I of SD Negeri Karanggedong through the cooperative model Numbered Heads Together (NHT). This research was conducted at Karanggedong State Elementary School with 39 students. The data source in this study used 2 data, primary and secondary data. Primary data were obtained from the results of student tests for each cycle, while secondary data were obtained from the observations of teachers and students during the study, student list, and documentation. Data collection techniques using test and non-test techniques. The data collection tools are in the form of test items and observation sheets. Data validation uses data triangulation. Data analysis in this study uses comparative descriptive. The results showed that there was an increase in mathematics learning outcomes material to calculate the area of the flat build class VI semester I of SD Negeri Karanggedong in the academic year 2015/2016. Learning outcomes during pre-cycle average class 57.31 increased to 76.89 in the first cycle and increased again in the second cycle to 84.64. The percentage of completeness of KKM 70 students which was originally 41.03% in pre-cycle increased to 74.36% in the first cycle and increased to 92.31% in the second cycle.